Insect meal as renewable source of food for animal feeding: a review - Sánchez-Muros, María-José; Barroso, Fernando G.; Manzano-Agugliaro, Francisco (Journal of cleaner production, 2014)
The massive utilisation in animal feeding of soy or fishmeal poses severe environmental issues. The insects could be a sustainable protein source. This article documents 150 species of insects that are currently commercially available in the EPPO (European and Mediterranean Plant Protection Organization) region and in North America. Furthermore, the various data regarding body composition are analysed. Amino acids and fatty acids of several insect species are compared with the composition of soy and fishmeal as principal protein sources for animal feeding. As a protein source, insects, depending on the species, have an adequate profile of amino acids. The more frequent limiting amino acids are histidine, lysine, and tryptophan, which could be incorporated into the diet. In conclusion, insects appear to be a sustainable source of protein with an appealing quantity and quality and acceptable nutritive properties. In conclusion, the use of insects as a sustainable protein rich feed ingredient in diets is technically feasible, and opens new perspectives in animal feeding. •The insects could be a renewable and sustainable protein source.•We review the properties of insect meal for animal feed.•Insects as feed ingredient can contribute to animal health.•Insects have great quantity and quality of protein with good nutritive properties.•This opens new perspectives of insect meal as a renewable source of protein.